2018
DOI: 10.1002/2017ms001113
|View full text |Cite
|
Sign up to set email alerts
|

Can We Use Single‐Column Models for Understanding the Boundary Layer Cloud‐Climate Feedback?

Abstract: This study explores how to drive Single‐Column Models (SCMs) with existing data sets of General Circulation Model (GCM) outputs, with the aim of studying the boundary layer cloud response to climate change in the marine subtropical trade wind regime. The EC‐EARTH SCM is driven with the large‐scale tendencies and boundary conditions as derived from two different data sets, consisting of high‐frequency outputs of GCM simulations. SCM simulations are performed near Barbados Cloud Observatory in the dry season (Ja… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…The 24-h-long simulations are initialized and driven by time-varying boundary conditions and large-scale forcings derived from the Integrated Forecasting System (IFS) of ECMWF. The method as applied here to drive the LES model was first described by Neggers et al (2012), and was recently used in slightly modified form in the study by Gesso and Neggers (2018). All fields provided to the LES as input are based on two analysis fields per day, at 0000 and 1200 UTC, supplemented by short-range forecast fields to cover the intermediate time points at 3, 6, and 9 h. This effectively yields a forcing dataset covering 24 h at 3-h time resolution, which is assumed sufficient to resolve diurnal and synoptic signals in the large-scale forcing.…”
Section: Initialization Boundary Conditions and Large-scale Forcingmentioning
confidence: 99%
“…The 24-h-long simulations are initialized and driven by time-varying boundary conditions and large-scale forcings derived from the Integrated Forecasting System (IFS) of ECMWF. The method as applied here to drive the LES model was first described by Neggers et al (2012), and was recently used in slightly modified form in the study by Gesso and Neggers (2018). All fields provided to the LES as input are based on two analysis fields per day, at 0000 and 1200 UTC, supplemented by short-range forecast fields to cover the intermediate time points at 3, 6, and 9 h. This effectively yields a forcing dataset covering 24 h at 3-h time resolution, which is assumed sufficient to resolve diurnal and synoptic signals in the large-scale forcing.…”
Section: Initialization Boundary Conditions and Large-scale Forcingmentioning
confidence: 99%
“…A sensitivity test that isolates these microphysical impacts from UP's grid resolution confirms that the microphysical settings are mostly responsible for the differences between SP and UP cloud feedback.Recent global simulations have predicted mostly positive and occasionally negative low cloud feedbacks with different magnitudes (Bretherton, 2015). Other studies have focused on cloud feedbacks in regional/single-column models (Dal Gesso & Neggers, 2018) or on only a particular cloud type. Xu et al (2010) studied the low cloud feedback to a change in sea surface temperature (SST) in the range of +4 K to an extreme +14 K. In a limited-area simulation of subtropical boundary layer cloud, they showed that the cloud feedback simulated by their large eddy simulation (LES), for this large range of SST increases is negative and is in the range of −0.7 to −5.2 W/m 2 /K with mostly negative contribution (−1.5 to 0.5 W/m 2 /K) from clear-sky feedback.…”
mentioning
confidence: 99%
“…cfSites includes high‐frequency output at different locations of instrumented sites and field campaigns, as well as a number of climate regimes where the inter‐model spread of cloud feedbacks is large (Bony et al., 2011). Dal Gesso and Neggers (2018) have used large‐scale forcings derived from the cfSites data to drive single column models and explored the boundary layer cloud response to climate change. The cfSites data has also been used to investigate the diurnal cycle of cloud feedbacks in GCMs (Webb et al., 2015).…”
Section: Methodsmentioning
confidence: 99%